Arkeologiska perspektiv på Westerhus ödekyrkogård på Frösön i Jämtland - Redin, Lars (Hikuin, 2000)
Archaelogical perspectives of the derelict churchyard of Westerhus at Frösön in Jämtland, Sweden By Lars Redin The excavation of the churchyard of Westerhus Church in Jämtland, Sweden, which was undertaken in the early 1950s, created the basis of epoch-making research into humane osteology (see for instance N.-G. Gejvall, 1960). The carefully stored and well-preserved skeleton material has made it possible to study the composition and life conditions of the population concerned. Unfortunately, the archaeological documentation has not enabled a corresponding research into the morphology of the grave material or the stratigraphical details, which could have thrown light on the relationship between the graves and the excavated church ruin. This has meant a considerable deficiency of the Westerhus material regarding source value and applicability, when compared with data from other excavated churchyards in Scandinavia. The present article attempts at compensating for this limitation. Using 71 photos kept in the cardboard boxes containing the skeleton material at the Statens Historiska Museum in Stockholm, a study in burial custom was undertaken. Creating a typological chronology concerning part of the grave material using a previously developed method was possible (see L. Redin 1976 and J. Kieffer-Olsen 1993 ). From the arm positions of the dead, a division into four types A, B, C, and D was possible. 14C dating of samples led to the conclusion that the churchyard was used for c.200 years, from the early 12th century until c.1300. A more thorough test of the 14C datings as compared the datings suggested by the arm positions is nescesary. The author rejects the theory that the stone church had a wooden predecessor. An appendix (by O. Kyhlberg and U. Strucke) discusses the possibilities and problems concerning the use of 14C dating.